Photophysical properties of alloxazine derivatives with extended aromaticity - Potential redox-sensitive fluorescent probe - Golczak, Anna; Insińska-Rak, Małgorzata; Davoudpour, Amirali; Hama Saeed, Daban; Ménová, Petra; Mojr, Viktor; Cibulka, Radek; Khmelinskii, Igor; Mrówczyńska, Lucyna; Sikorski, Marek (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2022)
The spectral and photophysical properties of two four-ring alloxazine derivatives, naphtho[2,3-g]pteridine-2,4(1H,3H)-dione (1a) and 1,3-dimethylnaphtho[2,3-g]pteridine-2,4(1H,3H)-dione, (1b) were studied. The propensity of 1a for excited-state proton transfer reactions in the presence of acetic acid as a catalyst was also studied, showing no signature of the reaction occurring. In addition, quenching of 1a fluorescence by acetic acid was investigated. Singlet and triplet states and spectral data for 1a and 1b were calculated using density functional theory TD-DFT at B3LYP/6-31G(d) and UB3LYP levels. Finally, fluorescence lifetime imaging microscopy (FLIM) using 1a and 1b as fluorescence probes was applied to in vitro human red blood cells (RBCs) with and without tert-butyl hydroperoxide (TB) as an oxidising agent. To evaluate and compare the effects of 1a and 1b on the redox properties of RBCs, the fluorescence lifetime, amplitude and fractional intensities were calculated, and phasor plot analysis was performed. The results obtained show the appearance of a new proximal cluster in the phasor fingerprint of RBCs in the presence of 1b and a shorter fluorescence lifetime of RBCs in the presence of 1a.
Keywords: Proton transfer; Microscopy, Fluorescence; Oxidation-Reduction; oxidace-redukce; Phasor analysis; fluorescenční mikroskopie; Alloxazines; fluorescenční barviva; Fluorescent Dyes; Quenching; flaviny; Flavins; Oxidative stress; Fluorescence